(untitled) (Journal of Analytical Oncology, 2013)
Nanomedicine, probably, is the future of modern medicine. Hence, there is a global effort being made in the development of nanopharmaceuticals. Among all the nano-pharmaceuticals developed so far, radiopharmaceuticals are the fewest in number of published studies. The development of nanoradiopharmaceuticals is complex but not impossible. In this work we discuss the possibility and the results of developing 4 nanoradiopharmaceuticals based on 3 different types of nanoparticles as alternative drug delivery systems. Also we present the preliminary results in animals.